Perancangan Media Sosialisasi Lagu Daerah Indonesia Menggunakan Pendekatan Electronic Dance Music - Virya Dharma Lim; Tony Wibowo (Journal of Information System and Technology (JOINT), 2020)
Traditional song in Indonesia are diverse from Sabang until Merauke, there are more than 200 songs traditional songs but most of people in Indonesia especially for teenagers don’t know about traditional songs in Indonesia because they thought traditional music are outdated for their era, because of that, teenagers in Indonesia mostly like music pop, rock and electronic. By designing traditional music with EDM arrangement will provide traditional song in a modern way and make teenagers in Indonesia know the traditional song indirectly. In this project we will use a software digital audio workstation (DAW) Ableton Live 9 and use research and development method with 4D model development (define, design, development, and dissemintae). The results of this project, produced a song entitled “Hey, Ampar-ampar Solo” with a duration of 5 minutes and 29 seconds. from the results of disseminate, the number of songs played was 57 times with 5 likes and 5 comments We hope by this project will make increase interest of Indonesian’s traditional songs for the people who are listening.